Shapeshifters: Black Girls and the Choreography of Citizenship - Inniss-Thompson, Misha N. (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
This review highlights Cox’s masterful ability explore how Black girls living in a Detroit homeless shelter navigate experiences with racism, poverty, and gender-based violence; talk back against stereotypes and controlling images; and highlight their right to citizenship.